The future is now: Model‐based clinical trial design for Alzheimer's disease. Issue 3 (27th December 2014) - Romero, K; Ito, K; Rogers, JA; Polhamus, D; Qiu, R; Stephenson, D; Mohs, R; Lalonde, R; Sinha, V; Wang, Y; Brown, D; Isaac, M; et al.
<x xml:space="preserve">Abstract</x> Failures in trials for Alzheimer's disease (AD) may be attributable to inadequate dosing, population selection, drug inefficacy, or insufficient design optimization. The Coalition Against Major Diseases (CAMD) was formed in 2008 to develop drug development tools (DDT) to expedite drug development for AD and Parkinson's disease.1 CAMD led a process that successfully advanced a clinical trial simulation (CTS) tool for AD through the formal regulatory review process at the US Food and Drug Administration (FDA) and European Medicines Agency (EMA).